Antibiotic Prophylaxis for Thyroid and Parathyroid Surgery: A Systematic Review and Meta-analysis. (March 2021) - Medas, Fabio; Canu, Gian Luigi; Cappellacci, Federico; Romano, Giorgio; Amato, Giuseppe; Erdas, Enrico; Calò, Pietro Giorgio
Objective: Although thyroid and parathyroid surgery is considered a clean procedure with a low incidence of surgical site infections (SSIs), a great number of endocrine surgeons use antibiotic prophylaxis (AP). The aim of this study was to assess whether AP is significantly effective in reducing the incidence of SSIs in this kind of surgery. Data Sources: A systematic literature search was performed with PubMed, Scopus, and ISI–Web of Science. Studies addressing the efficacy of AP in reducing the incidence of SSIs in thyroid and parathyroid surgery were included in the systematic review and meta-analysis. Review Methods: The random effects model was assumed to account for different sources of variation among studies. The overall effect size was computed through the inverse variance method. Heterogeneity across studies, possible outlier studies, and publication bias were evaluated. Results: A total of 6 studies with 4428 patients were included in the quantitative analysis. The incidence of SSI was 0.6% in the case group and 0.4% in the control group (odds ratio, 1.07; 95% CI, 0.3-3.81; P = .915). There was no evidence of heterogeneity among the studies ( Q = 8.36, P = .138; I 2 = 40.17). The analysis of several continuous moderators, including age, use of drain, and duration of surgery, did not generate any significant result. Conclusion: AP is not effective in reducing the incidence of SSI in thyroid and parathyroid surgery and should be avoided, notwithstanding the negative impact on social costs and the risk of development of antibiotic resistance.